Chawl-like housing in Mazagaon - Mumbai Archive Project Team (Jio Institute, 2024)
Chawls provided affordable housing solutions for the working-class population. Typically, a chawl is a multi-storeyed structure and has individual living units arranged around a central courtyard. The units open on a running balcony which is used to socialize with neighbours. The residential unit may include a bedroom, sitting room, and kitchen, though washroom facilities are usually common.